ANALISIS PENGARUH BAURAN PEMASARAN RITEL TERHADAP RETENSI KONSUMEN DI GIANT EKSPRES KEMILING - Rendi Agustian; Susi Indriyani (Jurnal Bisnis Darmajaya, 2019)
The objective to this research was to determine the effect of  retail mix consisting of products, prices, promotions, retail services and physical facilities on customer retention at Giant Ekspres Kemiling. The population in this study is the average number of buyers of Giant Express Kemiling for one month. Samples were taken as many as 364 respondents with purposive sampling technique. The data used is based on the results of respondents' answers using a Likert scale. Data processing used to answer the hypothesis is with the help of SPSS version 20. Based on the partial test results it is known that the retail service variable does not significantly influence customer retention, but the variables of product, price, promotion and physical facilities have a positive and significant influence on customer retention at the Giant Express Kemiling. While the results of simultan testing are known that  retail mix variables include; products, prices, promotions, retail services and physical facilities overall  simultaneously have a positive and significant influence on costumer retention at the Giant Express Kemiling.Keywords —Retail Mix, Costumer Retention